ICT and teacher education : the portuguese example - Gil, Henrique (1999)
Information and Communication Technologies (ICTs) are being use worldwide in every sector of society, however schools have not been permeated with them satisfactory. In Portugal, as in the rest in the world, several Projects have tried to introduce ICTs in schools in general and in classroom in particular. Teacher Training is therefore an important component. The research we have done focused in the Initial Teacher Training Institutions (Schools of Education – ESE) in Portugal that offers ICT in their curriculum as integrant part of teacher training. We gave an overview of the aims, contents, methodologies and evaluation of ICT subject in each School of Education.